The Effect of MgO Loads on Catalytic Activity of MgO/SiO2 in Coconut Oil Transesterification - Pandiangan, Kamisah Delilawati; Simanjuntak, Wasinton; Ilim, Ilim; Alista, Diska Indah; Noviana, Erika (Journal of Multidisciplinary Applied Natural Science, 2025)
This research aims to obtain biodiesel by transesterification of coconut oil with MgO/SiO2 as a catalyst, with the objective to examine the effect of MgO loads on the performance of the catalysts expressed in terms of oil conversion. The MgO/SiO2 composites with different mass ratios of 1:1, 1:2, 1:3, 1:5, and 1:10 were synthesized from Mg(NO3)·6H2O and SiO2 extracted from rice husk silica using sol-gel method and followed by calcination at 800 °C for 6 h. The produced catalysts were then tested in the transesterification of coconut oil to investigate the effect of catalyst composition, oil to methanol ratios, and reaction times. The experiments were carried out using a fixed catalyst load of 10% oil (w/v) and at 70 °C. The catalyst with the highest performance was then characterized by using X-ray diffraction (XRD) and scanning electron microscopy (SEM) to confirm the formation of crystalline MgO/SiO2. The highest conversion of the transesterification product was analyzed using gas chromatography-mass spectrometry (GC-MS) technique to confirm the biodiesel production. The XRD diffractogram of the synthesized sample is characterized by the presence of sharp peaks confirming the existence of the sample as crystalline material attributed to the pyroxene-ideal (MgO3Si) phase. The existence of the sample as crystalline material is also supported by the absence of a broad diffraction peak attributed to amorphous rice husk silica, and SEM image of the sample which is characterized by the visible existence of crystalline structure in the forms of platelet prismatic, and tetrahedral shaped structures. The results demonstrated that the highest conversion (98%) was achieved with the use of MgO/SiO2 (1:5) as a catalyst, a ratio of oil to methanol of 1:6, and a reaction time of 4 h. The formation of methyl esters was confirmed by the results of GC-MS analysis.